A fuzzy TOPSIS approach for home energy management in smart grid with considering householders' preferences - Sianaki, Omid; Masoum, Mohammad Sherkat (IEEE, 2013)
It is expected that demand response programs will be designed to decrease electricity consumption or shift it from on-peak to off-peak periods depending on consumers' preferences and lifestyles. This paper demonstrates a fuzzy TOPSIS decision-making approach to quantify and evaluate consumers' preferences at the micro-level when using electrical devices according to a real-time price scheme of demand response in order to best manage the use of appliances. This enables and supports householders to maximize their participation in demand response programs.